SOCIETAS PRIVATA EUROPAEA VERSUS SOCIETAS EUROPAEA - LUMINITA TULEASCA (Challenges of the Knowledge Society)
The stage of political procedures and negotiations related to the statute of a new European company: European Private Company triggers the analysing of the main features of such a company and comparing them to those of the companies regulated in Romania and on other member states of the European Union. Therefore, we shall have a complete picture on the organic statute of this new company and, especially, on the divergent aspects, aspects having prevented the enactment of the Regulation regarding European Private Company (Societas Privata Europaea).And not least, it is the only way to determine the extent the new trading company contributes to exceed the current issues of business development in the European Union, in which extent the European private company shall represent or not a progress in the matter of European trading companies, where the main mark is represented by the European Company (Societas Europaea).